A virtual keyboard security system for automated teller machine - Brindha Devi, V; Sindhuja, S; Shanthini, S; Hemalatha, M (International Journal of Engineering and Technology, 2018)
The Automated Teller Machines (ATM) are used for cash withdrawals. Meanwhile as ATM lacks security, thefts occurring in the ATMs are also high. Our proposed system minimizes those break-ins occurring in the ATMâ€™s by instigating a low cost standalone embedded sys-tem using Arduino Microcontroller. This system is proposed for ATM security, comprising of the components namely RGB tag, Global System for Mobile communication (GSM), Global Positioning System (GPS), Virtual Keyboard and camera. Authentication by virtual keyboard thus helps the public to protect their credentials from being captured by malicious bots, key loggers and spyware. Whenever theft occurs, Buzzer makes an alarm, DC Motor turns ON and the door of ATM is closed. The nearby police station and corresponding bank authorities is alerted by the GSM Modem that sends messages along with the location. This will prevent the robberies and the person in-volving in the robbery can be easily caught. In short, it discusses the methods that are used to detect the venture, initiate preemptive measures and forewarn the officials through GSM network. This system thus heightens the safety of ATM users as well as the ATMâ€™s against forthcoming attacks effectively.Â Â